Pengelolaan Program Taman Bacaan Masyarakat Paguyuban Pemuda Literasi Global (TBM PPLG) Dalam Meningkatkan Budaya Literasi Masyarakat di Lopang Gede Kelurahan Lopang Kecamatan Serang Kota Serang - Siti Nurohayati; Ahmad Fauzi; Herlina Siregar (Journal on Education, 2023)
Community Reading Center (TBM) program innovation is a new creative idea or idea, method, or tool that is systematically planned by someone, and approved by everyone to be implemented continuously in the organization so that the benefits can be felt by many people. This study aims to describe the management of the global literacy youth community reading garden program (TBM PPLG) in improving the culture of community literacy in Lopang Gede, Lopang Subdistrict, Serang District, Serang City. The research method uses a descriptive with a qualitative approach. Research subjects included the founder, chairman, 3 volunteers, 4 learning residents, and 4 surrounding communities. Data collection techniques in this study namely; observation, interview, and documentation. Data analysis techniques used that is; data reduction, data data display, and conclusion drawing/verification. The results showed that the management of the global literacy youth association community reading center program (TBM PPLG) in improving the culture of community literacy in Lopang Gede, Lopang Subdistrict, Serang District, Serang City, has been going well with the use of four management functions namely; stage Planning, organizing, Actuating, and Controlling.